Status Pengelolaan Sumberdaya Ikan Demersal Sekitar Pantai di Kabupaten Indramayu, Jawa Barat - Gatot Yulianto; Kadarwan Suwardi; Luky Adrianto; Machfud Machfud (Journal Omni-Akuatika, 2016)
The status of fish resources in management fisheries context is important to be known for settingresources policy in order to ensure continuity of fish stock and harvest. Estimating the level ofsustainable catches and economic rent by  using surplus production approach and Gordon-Schaeferbioeconomic analysis then comparing the actual condition, it will point to level of resource exploitationand level of resource degradation. The management of demersal fish around the beach in IndramayuRegency which is characterized by open access resource indicate the status of the fish resource in astate of overfishing and degraded. Therefore, it is important for designing fisheries managementpolicy by regulating the amount of fishing effort.Keywords: demersal fish, bioeconomic analysis, overfishing, degradation